2017
DOI: 10.1002/jor.23211
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of autologous synovial mesenchymal stem cells promotes meniscus regeneration in aged primates

Abstract: Transplantation of aggregates of synovial mesenchymal stem cells (MSCs) enhanced meniscus regeneration in rats. Anatomy and biological properties of the meniscus depend on animal species. To apply this technique clinically, it is valuable to investigate the use of animals genetically close to humans. We investigated whether transplantation of aggregates of autologous synovial MSCs promoted meniscal regeneration in aged primates. Chynomolgus primates between 12 and 13 years old were used. After the anterior hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…In our current study we used BMP7 due to its availability in our laboratory. We previously examined the dose effect of BMP7 on in vitro cartilage formation of synovial MSCs and 1 μg/ml BMP7 formed the largest cartilage pellets, therefore, 1μg/ml BMP7 was used in this study as well as in other such studies [7, 27, 41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…In our current study we used BMP7 due to its availability in our laboratory. We previously examined the dose effect of BMP7 on in vitro cartilage formation of synovial MSCs and 1 μg/ml BMP7 formed the largest cartilage pellets, therefore, 1μg/ml BMP7 was used in this study as well as in other such studies [7, 27, 41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…When chondrogenic differentiation was induced with BMP-2, TGF-β and dexamethasone in 3D pellet culture, synovial-derived MSCs consistently produce larger cartilaginous pellets than bone marrow MSCs from the same patients (Shirasawa et al, 2006). Intra-articular injection of SM-MSCs in rat, rabbit, porcine and primate meniscal defect and injury models have shown that SM-MSCs can promote meniscus regeneration and provide protection of medial femoral articular cartilage (Hatsushika et al, 2013, 2014; Ozeki et al, 2015; Kondo et al, 2016). In early clinical trials SM-MSCs have shown promise for treatment of articular cartilage defects, producing hyaline cartilage repair tissue (Sekiya et al, 2015).…”
Section: Tissue Reservoirs Of Mscsmentioning
confidence: 99%
“…Prior studies have reported promising results in meniscal regeneration utilizing meniscus ECM preparations in allograft [16,20,70], hydrogel [43,44], and soluble [46] forms; MSCs derived from the bone marrow [7173], synovium [29], and meniscus [23,31]; and evaluation in animal models ranging from subcutaneous implantation [43,45] to intra-articular injections in rats [29,31,72] up to primates [74]; but none have studied the combination of MSCs and meniscus ECM hydrogel at their relevant site of action. We demonstrate the use of decellularized bovine meniscus hydrogel for intra-articular delivery of human mesenchymal stem cells in an orthotopic nude rat model of meniscal injury.…”
Section: Discussionmentioning
confidence: 99%